Aplicación de la química en la pequeña industria como asignatura optativa y su incidencia en el desarrollo de habilidades en los estudiantes del primer año de bachillerato en ciencias del colegio Emiliano Ortega Espinoza del cantón Catamayo provincia de Loja periodo lectivo 2012 – 2013. Lineamientos propositivos - Soto Collaguazo, Alba Cristina (2015)
The Application of the chemistry in the Small Industry is in charge of the extraction and prosecution of the matters cousins, so much natural as synthetic, and of its transformation in other substances with characteristic different from those that had originally, to satisfy the necessities of people improving its quality of life. Their objective is to elaborate a product of good quality with the possible lower cost, and trying to cause the smallest damage possible to the environment. The matters cousins correspond to diverse extracted materials of the nature with the purpose of manufacturing consumption goods. In this mark the present investigation has as title: APPLICATION OF THE CHEMISTRY IN THE SMALL INDUSTRY LIKE OPTIONAL SUBJECT AND THEIR INCIDENCE IN THE DEVELOPMENT OF ABILITIES IN THE STUDENTS THE FIRST years old IN SCIENCES OF THE SCHOOL EMILIANO ORTEGA ESPINOZA OF THE CANTON CATAMAYO COUNTY DE LOJA PERIOD LECTIVO 2012 - 2013. LIMITS PROPOSITIVOS. The same one that was structured and it developed from conformity to the graduation regulation in validity of the National University of Loja. Their general objective was: To propitiate the application of the chemistry in the small industry with experiments of easy elaboration with the purpose of developing abilities in the students of the School Emiliano Ortega Espinoza. The used methods were: the inductive, deductive, analytic, interpretive, statistical-descriptive, synthetic, bibliographical method. For the obtaining of information; surveys were applied at 3 educational and to 50 students the First years old. At the end of the investigation and after the analysis of the results, it was determined the following conclusions: that the laboratory doesn't have materials, reagents and teams that allow the realization of the practices. The equally little contents contribute to select the practices to be carried out and the educational ones don't also have a methodological guide for the realization of the practices of an organized one. " Key words: Application of the chemistry, development of abilities.